Hubungan Faktor Individu, Faktor Organisasi, dan Faktor Psikologi dengan Kepatuhan terhadap Clinical Pathway pada Profesional Pemberi Asuhan di RSGM Gusti Hasan Aman - Sembiring, Asriyani Br; Nugroho, Adi; Noor, Zairin; Herawati, Herawati; Husaini, Husaini (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Efforts to improve the quality of health services are carried out by measuring quality indicators. One of the quality indicators measured is compliance with the clinical pathway. Given the large role of clinical pathway, the implementation of clinical pathway is important in hospitals. However, from the RSGM Gusti Hasan Aman Quality Committee report from 2017-2023 compliance with the clinical pathway at RSGM Gusti Hasan Aman has not yet reached the national quality standard. This is considered to be related to individual factors, organizational factors, psychological factors, and knowledge of care professionals. This study aims to analyze the relationship between individual factors, organizational factors, and psychological factors with compliance of clinical pathways in professional caregivers at the Outpatient Unit of RSGM Gusti Hasan Aman. This study is a quantitative study using an analytic observational method with a cross-sectional approach. The sample in this study were Professional Care Givers in the Outpatient Unit of RSGM Gusti Hasan Aman. The sample size was taken with a proportionate stratified random sampling technique of 83 respondents, consisting of 32 dental asisstant, 29 dentists, and 22 specialist dentists. The results of the statistical test show that there is no relationship between individual factors (age, gender, education, tenure, marital status) with compliance of clinical pathway. There is a relationship between organizational factors, namely leadership (p=0.019) with compliance of clinical pathways, but other organizational factors, namely human resources and rewards have no relationship with compliance of clinical pathways. There is a relationship between psychological factors, namely attitude towards clinical pathway (p=0.003), work motivation (p=0.008), and perceived benefits of clinical pathway (p=0.008) with compliance of clinical pathway. From multivariate results, it was found that attitude towards clinical pathway (p=0.013) had a significant relationship with compliance of clinical pathway. So, there is relationship between leadership, attitude, motivation, and perceived with compliance of clinical pathways. And attitudes towards clinical pathways have a significant relationship with compliance of clinical pathways. Keywords: Individual Factors, Organizational Factors, Psychological Factors, Compliance of Clinical Pathway  ABSTRAK Upaya peningkatan mutu pelayanan kesehatan dilakukan dengan pengukuran indikator mutu. Salah satu indikator mutu yang diukur adalah kepatuhan terhadap clinical pathway. Mengingat besarnya peranan clinical pathway, maka pelaksanaan clinical pathway menjadi penting di rumah sakit. Namun, dari laporan Komite Mutu RSGM Gusti Hasan Aman dari tahun 2017-2023 kepatuhan terhadap clinical pathway di RSGM Gusti Hasan Aman belum mencapai standar nasional mutu. Hal ini dinilai berhubungan dengan faktor individu, faktor organisasi, dan faktor psikologi para profesional pemberi asuhan.  Penelitian ini bertujuan untuk menganalisis hubungan faktor individu, faktor organisasi, faktor psikologi, dan pengetahuan dengan kepatuhan terhadap clinical pathway pada profesional pemberi asuhan di Unit Rawat Jalan RSGM Gusti Hasan Aman Kalimantan Selatan. Penelitian ini merupakan penelitian kuantitatif menggunakan metode observasional analitik dengan pendekatan cross-sectional. Sampel pada penelitian ini adalah Profesional Pemberi Asuhan di Unit Rawat Jalan RSGM Gusti Hasan Aman. Besar sampel diambil dengan teknik proportionate stratified random sampling sebanyak 83 responden, yang terdiri dari 32 terapis gigi dan mulut, 29 dokter gigi, dan 22 dokter gigi spesialis. Dari uji statistik pada penelitian ini didapati tidak ada hubungan antara faktor individu (usia, jenis kelamin, pendidikan, masa kerja, status pernikahan) dengan kepatuhan terhadap clinical pathway. Ada hubungan antara faktor organisasi, yaitu kepemimpinan (p=0,019) dengan kepatuhan terhadap clinical pathway, namun faktor organisasi lain, yaitu sumber daya manusia dan imbalan atau reward tidak ada hubungan dengan kepatuhan terhadap clinical pathway. Ada hubungan antara faktor psikologi, yaitu  sikap terhadap clinical pathway (p=0,003), motivasi kerja (p=0,008), dan persepsi manfaat clinical pathway (p=0,008) dengan kepatuhan terhadap clinical pathway. Dari hasil multivariat, didapati sikap terhadap clinical pathway (p=0,013) merupakan variabel yang paling berhubungan bermakna dengan kepatuhan terhadap clinical pathway. Jadi, disimpulkan ada hubungan kepemimpinan, sikap, motivasi, dan persepsi dengan kepatuhan terhadap clinical pathway. Dan sikap terhadap clinical pathway memiliki hubungan paling bermakna dengan kepatuhan terhadap clinical pathway. Kata Kunci: Faktor Individu, Faktor Organisasi, Faktor Psikologi, Kepatuhan Terhadap Clinical Pathway